Peran Koperasi dalam Meningkatkan Kesejahteraan Masyarakat - Nur Wulan Ramdhaniah; Dini Selasi (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
Cooperatives are economic institutions that play a vital role in improving community welfare through the principles of family and mutual cooperation. This study aims to determine the role of cooperatives in improving community welfare and the factors that support and hinder cooperative development. The research method used was a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation. Data were obtained from cooperative administrators, cooperative members, and community members involved in cooperative activities. The results of the study indicate that cooperatives play a role in improving community welfare by providing business capital, providing savings and loan services, creating jobs, and increasing members' incomes. Furthermore, cooperatives are able to strengthen social solidarity and encourage community economic empowerment. Sharia cooperatives provide additional contributions through the application of Islamic economic principles that emphasize justice and mutual assistance. However, cooperatives still face several obstacles such as low human resource quality, limited capital, and less than optimal use of digital technology. Based on the research results, it can be concluded that cooperatives play a strategic role as pillars of the people's economy in improving community welfare. Therefore, more professional, innovative, and technology-based cooperative management is needed so that cooperatives can develop sustainably and provide broader benefits to the community.